A fugacity‐based toxicokinetic model for narcotic organic chemicals in fish. (7th March 2016) - Celsie, Alena; Mackay, Donald; Parnis, J. Mark; Arnot, Jon A.
Abstract: A novel dynamic fugacity‐based model is described, developed, and tested that simulates the uptake of narcotic organic chemicals in fish from water as occurs in aquatic bioconcentration and toxicity tests. The physiologically based toxicokinetic model treats the time course of chemical distribution in 4 compartments (tissue groups) in the fish, including the liver, in which biotransformation may occur. In addition to calculating bioconcentration and toxicokinetics, 5 possible toxic endpoints are defined corresponding to chemical concentration, fugacity, or activity reaching a critical value that causes 50% mortality. The mathematical description of multicompartment uptake is simplified by expressing the equations in the fugacity format. The model is parameterized and tested against reported empirical data for the bioconcentration of pentachloroethane in rainbow trout and for uptake and mortality from aquatic exposures to naphthalene and 1, 2, 4‐trichlorobenzene in fathead minnows. Model performance is evaluated, and it is concluded that with suitable parameterization it has potential for application for assessment of both bioconcentration and toxicity expressed as median lethal concentrations, critical body residues, and chemical activity as a function of time to death. Environ Toxicol Chem 2016;35:1257–1267. © 2015 SETAC